788. Enterobacter cloacae Infection Characteristics and Outcomes in Military Personnel who Sustained Trauma in Iraq and Afghanistan. (4th December 2021) - Bennett, William N; Yabes, Joseph; Mende, Katrin; Beckius, Miriam; Rahman, Azizur; Tribble, David
Abstract: Background: Enterobacter cloacae is a Gram-negative rod with chromosomally-induced Amp-C β-lactamase with multidrug-resistant potential. Joint Trauma System guidelines for treating combat wounds include prophylaxis with cefazolin and ertapenem, potent inducers of Amp-C. We evaluated clinical characteristics, antibiotic utilization, and outcomes associated with battlefield-related E. cloacae infections. Methods: All initial solitary (those with single isolates) and serial E. cloacae isolates (≥24 hours from initial isolate from any site) were collected from the Trauma Infectious Disease Outcomes Study (6/2009-12/2014). Inclusion required E. cloacae isolation from a clinical infection. Amp-C-inducing β-lactams were classified based on induction potential and lability to the Amp-C β-lactamase as Amp-C induction levels. Results: Of 653 E. cloacae isolates, 253 met inclusion criteria – 64 patients had only initial isolates, 54 patients had serial isolates. Patients were largely male (99%), median age 23 years (IQR 21-27), with injury severity score of 34 (IQR 24-45). Initial isolates were wound (70%), respiratory (22%), blood (7%), urine (1%), and other (1%). Patients commonly had blast injuries (89%), required ICU admission (95%), and had a median hospital stay of 57 days (IQR 39-82). Patients with serial isolates showed a trend towards earlier clinical infection (5 vs 8 days, P = 0.07). They were also less likely to receive carbapenems prior to E. cloacae isolation compared to those with only initial isolates (4% vs 38%) and more likely to receive 1 st generation cephalosporins (79% vs 58%, P = 0.01). The serial isolate group received more days of 1 st generation cephalosporins (median 6 days vs 2.5 days, P = 0.01). Cumulative antimicrobial therapy trended towards significance and was greater with the serial isolates (median 100 days vs 74 days, P = 0.08). There was no difference in number of surgical interventions between those with and without serial isolates (P = 0.54). Overall, 6 patients died. Conclusion: E. cloacae infections after battlefield trauma were frequently encountered and associated with exposure to 1 st generation cephalosporins. Serial infections did not correlate to worse patient outcomes but displayed a trend towards an overall greater duration of antibiotic use. Disclosures: William N. Bennett, V, MD, Abbvie (Shareholder)Amgen (Shareholder)Nabriva (Shareholder)